(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2019)
The research objective of the Analysis of Use of FUNCTION on Job Data in Karakan Village was to publish the most important form of livelihood in Karakan village 06. The method used for this study was to use the FUNCTION method. the results derived from this study are that we can find out the percentage of the most work as livelihoods in Karakan village 06.